The impact of using the Edmodo educational platform on the development of cognitive achievement and motivation towards learning mathematics among eleventh grade students in the governorate of South Al Batinah in Sultanate of Oman - Al-Bhri, Fahad Moosa Anas (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to investigate the impact of the Edmodo educational platform on developing cognitive achievement and raising motivation toward learning mathematics for eleventh- grade students in Batinah South Governorate in the Sultanate of Oman. The study was based on a semi- experimental design and the sample of the study consisted of (40) students divided into two groups: a controlled group using the traditional one and an experimental group using the educational platform. The achievement test and the motivation scale were used as data collection tools and statistical treatments were carried out to test the hypotheses of the study. The results of the study revealed that the use of the educational platform Edmodo contributed to the development of achievement and raising the motivation of the experimental group. The development of cognitive achievement and raising the motivation towards learning in mathematics for grade eleventh students. The study recommended employing educational platforms in general and the Edmodo platform in particular in teaching mathematics because of its functional role.